As máscaras da modernidade : uma leitura do ser e do poder no romance A caverna, de José Saramago - Leonardo, Devalcir (2008)
This paper aims to build an analytical interpretive reading of the book A Caverna (2000), by José Saramago, from a critical literary perspective, based on the theories by George Lukács, Ferenc Fehér, Michel Foucault and Martin Heidegger. After a theoretical recovery of the critical line chosen, including the narrative genre structural elements, going deeply in the philosophical concepts presented in the plot of the novel, as well as, an allegory of Pluto's cave, present in the book, made up by a panel of modern human existence. To do that, an analysis was made bout the power game in the book. In that way, discipline is made up in the novel A Caverna, in the way of living in the Centro (downtown), a place full of guards and video cameras watching every thing. In this space, the Michel Foucault's theory in Vigiar e Punir (1987) makes clear the power relations carried out an instrument at the service of the market and, through that instrument, people are watched, becoming gentle and harmless for the system. In the themes of the novel A Caverna, there are the updating of the platonic myth and the description of the capitalist society shadows through the consumption and the search for this society liberation based on leaving the Centro. To do a philosophical reading, the book Ser e Tempo (2001) by Martin Heidegger was used, as well as his reflection on the existence of the modern man.